Analisis Dampak Kebijakan Audit Dana Desa Dengan Menggunakan Aplikasi Sistem Pengawasan Keuangan Desa Oleh Inspektorat Kota Prabumulih - Marleansyah, Eko Subri; Novaria, Eva; Iriani, Atrika (@-Publik: Jurnal Administrasi Publik, 2023)
The Village Financial Monitoring System application uses Microsoft SQL Server. The size of this database is relatively large because it is based on the Village Financial Oversight System Application database in the form of a budget compilation report and the realization of the Village APBDes at the District/City Level. The main requirement for the Village Financial Monitoring System Application to work is that districts/cities and villages in their area have implemented the Village Financial Monitoring System Application. In order for the Village Financial Supervision System Application to run optimally, technical requirements are required for application users, namely: The computer has Microsoft SQL Server installed and the Village Financial Supervision System Application database is available at the district level compilation. The purpose of this study is to analyze the Impact of the Village Fund Audit Policy using the Village Financial Monitoring System Application by the Prabumulih City Inspectorate. The things that were identified were: The Government Internal Supervisory Apparatus (APIP) at the Prabumulih City Inspectorate had not yet mastered the application of the Village Financial Oversight System and limited knowledge and understanding of human resources, ineffective communication between the Prabumulih City Inspectorate and village officials. The data analysis technique used in this study is a qualitative data analysis technique. This study shows that: using the Village Financial Oversight System Application has had a positive impact on village fund audit policies. Even though there are still obstacles/obstacles with the Village Fund Audit Policy by using the Village Financial Oversight System Application such as the Government Internal Supervisory Apparatus (APIP) at the City Inspectorate Prabumulih has not mastered the application of the Village Financial Oversight System as well as limited knowledge and understanding of human resources, ineffective communication between the Prabumulih City Inspectorate and village officials